2012
DOI: 10.1002/ppul.22712
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous hemopneumothorax simulating acute abdominal affections

Abstract: Spontaneous hemopneumothorax (SHP) is a rare potentially life-threatening condition that occurs in predominantly young adolescents. The resultant massive hemorrhage leading to hypovolemic shock can be a surgical emergency. It constitutes 1-12% of all spontaneous pneumothoraces and presents with two cardinal features, chest pain and dyspnea. However, the pain of SHP may be confined to the abdomen secondary to the irritation of diaphragmatic pleura, which produces signs simulating an acute abdomen. SHP masquerad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In contrast, conservative treatment may result in hypovolemic shock secondary to massive hemorrhage with a mortality rate of up to 33%. 14 However, research has shown that it is difficult to determine the source of bleeding in patients with SHP, especially during the initial VATS procedure. 15 This may be because the collapsed lung loses its local filling ability, and blood from even small vessels can freely flow into the chest cavity, resulting in a large amount of blood loss and hemorrhagic shock.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, conservative treatment may result in hypovolemic shock secondary to massive hemorrhage with a mortality rate of up to 33%. 14 However, research has shown that it is difficult to determine the source of bleeding in patients with SHP, especially during the initial VATS procedure. 15 This may be because the collapsed lung loses its local filling ability, and blood from even small vessels can freely flow into the chest cavity, resulting in a large amount of blood loss and hemorrhagic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal rigidity is probably produced by basal pleurisy. Besides the simulation of gallbladder disease [36], SHP may also simulate appendicitis, bleeding peptic ulcer, or even perforated peptic ulcer.…”
Section: Minimal Pediatric Thoracic Surgery In Taiwanmentioning
confidence: 99%